Experimental Investigation of Microstructure and Mechanical Properties of TIG Welded Aluminium Alloys - Balasubramanian, R. R.; P., Vijayasarathi; Venkatamuni, T.; Kannan, S. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
Aluminium and its alloys are used in fabrication because of their low weight, good corrosion resistance and weldability. Pure aluminium is soft and therefore not suitable for structures, which require strength. The Present investigation aims to compare the mechanical properties of non-heat treatable Aluminium alloy AA5083 and heat treatable. Aluminium alloy AA7020 using Tungsten Inert Gas welding. 5556A filler were used to weld AA7020 alloy and 5183A filler for AA5083 alloy. Effect of pulsing mode over conventional mode of GTA process were also investigated for AA5083 alloy. In this work, gas tungsten arc welding process has been selected because it is low heat input process. Low heat input process has selected because AA7020 and AA5083 were low melting point material. The alternating current (AC) power source has been selected because of better cleaning action and high heat concentration on the materials can be avoided. Mechanical testing like tensile test, impact test, bend and hardness test have been critically analysed and the properties were summarized and correlating with microstructure and SEM fractographs.